On-site rapid detection method for trace heavy metals in domestic drinking water
By using heavy metal-enriched particulate resin for dispersed solid phase extraction in XRF detection, the problem that XRF is difficult to detect trace heavy metals in liquid samples is solved, and the rapid and sensitive detection of trace heavy metals in domestic drinking water is achieved, and the detection requirements of μg/L level are met.
Patent Information
- Application Number
- CN202411906139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-29
AI Technical Summary
Existing X-ray fluorescence spectroscopy (XRF) is difficult to directly detect trace heavy metals in liquid samples, especially in drinking water. Due to the poor signal-to-noise ratio and high uncertainty, the detection limit is usually above mg/L, and cannot meet the detection requirements of the μg/L level.
Heavy metal-enriched particulate resin is used for dispersed solid phase extraction. By adding the resin to the sample-loading bottle filled with drinking water, it is fully shocked to enrich trace heavy metals, and then using XRF to detect the enriched samples, quantitative analysis of the heavy metal content in water is achieved.
It realizes rapid enrichment and detection of trace heavy metals in domestic drinking water, has high sensitivity and wide application range, and can detect multiple heavy metals (Cd, Tl, Pb, Hg) at the same time, and the detection limit can reach 2μg/L, meeting the requirements for heavy metals for domestic drinking water.
Smart Images

Figure CN119901770A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of XRF detection technology, and in particular to a method for rapid on-site detection of trace heavy metals in drinking water. Background Art
[0002] X-ray fluorescence spectrometry (XRF) is a green and environmentally friendly non-destructive multi-element simultaneous analysis and detection method, which is widely used in the analysis of major, minor and trace elements in environmental samples. In recent years, portable X-ray spectrometers (XRF) have been widely used in the analysis of trace elements in geological materials. They have the characteristics of small size, light weight, fast analysis speed and on-site non-destructive detection, and can achieve qualitative and quantitative analysis based on the characteristic X-ray fluorescence energy, wavelength and intensity emitted by heavy metals when they are excited to a high energy state. However, XRF technology is usually used to analyze environmental solid samples. When directly analyzing liquid samples, the high scattering background of X-rays, poor signal-to-noise ratio and high uncertainty of the results obtained have resulted in its application being limited, and the detection limit is generally above mg / L.
[0003] However, due to the excessive attenuation loss of X-rays in water and weak penetration, it is difficult to effectively excite the target analytes, and it is still difficult to directly use them to detect heavy metal ions in water. At the same time, the content of heavy metal elements in general natural water bodies or drinking water for residents is in the concentration range of μg / L, while the detection limit of X-ray fluorescence spectrometer is generally in mg / L, which makes it almost impossible to directly use X-ray fluorescence spectrometer to detect trace heavy metals in water samples.
[0004] Therefore, in order to make the portable XRF equipment meet the detection requirements of μg / L level trace analytes in liquid samples, a pre-enrichment method is generally used to enrich the target substance in the liquid sample through the enrichment material, so that the target substance content in the liquid sample in the enrichment material is increased to above the detection limit of the XRF equipment, thereby realizing the content detection of the target substance in the liquid sample.
[0005] However, in the current on-site detection process, the use of an enrichment head in conjunction with a syringe for enrichment is time-consuming and labor-intensive, and the use of an extraction device for enrichment has complex and fragile device accessories, which is not conducive to rapid on-site detection. It also requires carrying too much equipment, and the detection process is complicated.
[0006] Therefore, there is an urgent need for an on-site rapid detection method for trace heavy metals in drinking water. Summary of the invention
[0007] The present application provides an on-site rapid detection method for trace heavy metals in drinking water, comprising:
[0008] Adding heavy metal enriched granular resin into a sample loading bottle containing drinking water, and fully shaking for a first preset time, so that the heavy metal enriched granular resin as a dispersed solid phase can enrich and extract trace heavy metals in the drinking water, collecting the heavy metal enriched granular resin to prepare a sample to be tested, using XRF to detect the heavy metal signal of the sample to be tested, and calculating the heavy metal content in the water;
[0009] Drinking water includes drinking water and water used for human life.
[0010] In some optional embodiments of the present application, the heavy metal-enriched granular resin is an ion exchange resin or a chelating resin.
[0011] In some optional embodiments of the present application, the heavy metal-enriched granular resin is an ion exchange resin containing methyl mercaptan functional groups.
[0012] In some optional embodiments of the present application, the heavy metal-enriched granular resin is Cohis CH-97 resin.
[0013] In some optional embodiments of the present application, the particle size of the heavy metal-enriched granular resin ranges from 75 to 450 μm.
[0014] In some optional embodiments of the present application, the volume of drinking water ranges from 15 to 500 mL.
[0015] In some optional embodiments of the present application, the first preset duration ranges from 2 to 20 minutes.
[0016] In some optional embodiments of the present application, the first preset duration is 10 minutes.
[0017] In some optional embodiments of the present application, the sample to be tested made of heavy metal-enriched granular resin is a round cake with a thickness of 2 to 6 mm and a diameter of 3 to 10 mm.
[0018] In some optional embodiments of the present application, the thickness of the sample to be tested is 2 to 3 mm.
[0019] In some optional embodiments of the present application, the thickness of the sample to be tested is 3 mm and the diameter is 8 mm.
[0020] In some optional embodiments of the present application, XRF detection is performed after drying.
[0021] In some optional embodiments of the present application, the sample to be tested is dried by absorbing water with filter paper or by drying.
[0022] In some optional embodiments of the present application, the XRF is a monochromatic portable X-ray fluorescence spectrometer.
[0023] In some optional embodiments of the present application, the heavy metal includes at least one element of Cd, Tl, Pb, and Hg.
[0024] In some optional embodiments of the present application, the heavy metal includes at least one element of Cd, Tl, and Pb.
[0025] The on-site rapid detection method for trace heavy metals in drinking water based on dispersed solid phase extraction provided by the present application can realize the rapid enrichment and detection of trace heavy metals in drinking water, and has the characteristics of being able to detect multiple heavy metals (Cd, Tl, Pb, Hg) at the same time, and high sensitivity. Using the dispersed solid phase extraction method, the heavy metal enrichment granular resin materials available on the market can be used, and there is no need to specially develop extraction membranes and column materials of specific shapes, which expands the scope of application and ease of use of the technology. This method can make the enriched drinking water to be tested be discharged through the filter by squeezing the sample loading bottle, without the need to use positive or negative pressure equipment, avoiding the need to carry additional equipment for field operations. The method has a wide range of applicability to water sample volume and can achieve high-multiple enrichment of heavy metals in water. The method has a low detection limit for heavy metals in drinking water, and the detection limit for Cd, Pb, and Tl elements can reach 2μg / L, which meets the requirements for heavy metal detection in drinking water, and the spike recovery experiment verifies that the detection results of this method are highly credible. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a schematic diagram of the change in the absorption rate of heavy metals detected by the granular resin CH-97 of the present application example with the increase of the oscillation adsorption time for different targets;
[0028] Figure 2 This is a schematic diagram showing the effect of the thickness of the disc sample to be tested made of granular resin CH-97 on the count value of each ion;
[0029] Figure 3 This is a schematic diagram of the effect of different sample diameters on monochromatic XRF measurement in the embodiments of the present application;
[0030] Figure 4 This is a schematic diagram of the changes in the monochromatic XRF count values of different heavy metals using different drying methods in the embodiments of this application;
[0031] Figure 5This is a standard curve diagram of the initial concentration of each heavy metal ion and the monochromatic XRF count value of the particle resin oscillation method in the examples of this application. DETAILED DESCRIPTION
[0032] The technical solution of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0033] In the description of the present application, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.
[0034] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0035] The present application provides an on-site rapid detection method for trace heavy metals in drinking water, comprising:
[0036] Adding heavy metal enriched granular resin into a sample loading bottle containing drinking water, and fully shaking for a first preset time, so that the heavy metal enriched granular resin as a dispersed solid phase can enrich and extract trace heavy metals in the drinking water, collecting the heavy metal enriched granular resin to prepare a sample to be tested, using XRF to detect the heavy metal signal of the sample to be tested, and calculating the heavy metal content in the water;
[0037] Drinking water includes drinking water and water used for human life.
[0038] In some optional embodiments of the present application, the heavy metal-enriched granular resin is an ion exchange resin or a chelating resin.
[0039] In some optional embodiments of the present application, the heavy metal-enriched granular resin is an ion exchange resin containing methyl mercaptan functional groups.
[0040] In some optional embodiments of the present application, the heavy metal-enriched granular resin is Cohis CH-97 resin.
[0041] In some optional embodiments of the present application, the particle size of the heavy metal-enriched granular resin ranges from 75 to 450 μm.
[0042] In some optional embodiments of the present application, the volume of drinking water ranges from 15 to 500 mL.
[0043] In some optional embodiments of the present application, the first preset duration ranges from 2 to 20 minutes.
[0044] In some optional embodiments of the present application, the first preset duration is 10 minutes.
[0045] In some optional embodiments of the present application, the sample to be tested made of heavy metal-enriched granular resin is a round cake with a thickness of 2 to 6 mm and a diameter of 3 to 10 mm.
[0046] In some optional embodiments of the present application, the thickness of the sample to be tested is 2 to 3 mm.
[0047] In some optional embodiments of the present application, the thickness of the sample to be tested is 3 mm and the diameter is 8 mm.
[0048] In some optional embodiments of the present application, XRF detection is performed after drying.
[0049] In some optional embodiments of the present application, the sample to be tested is dried by absorbing water with filter paper or by drying.
[0050] In some optional embodiments of the present application, the XRF is a monochromatic portable X-ray fluorescence spectrometer.
[0051] In some optional embodiments of the present application, the heavy metal includes at least one element of Cd, Tl, Pb, and Hg.
[0052] In some optional embodiments of the present application, the heavy metal includes at least one element of Cd, Tl, and Pb.
[0053] The on-site rapid detection method for trace heavy metals in drinking water based on dispersed solid phase extraction provided by the present application can realize the rapid enrichment and detection of trace heavy metals in drinking water, and has the characteristics of being able to detect multiple heavy metals (Cd, Tl, Pb, Hg) at the same time, and high sensitivity. Using the dispersed solid phase extraction method, the heavy metal enrichment granular resin materials available on the market can be used, and there is no need to specially develop extraction membranes and column materials of specific shapes, which expands the scope of application and ease of use of the technology. This method can make the enriched drinking water to be tested be discharged through the filter by squeezing the sample loading bottle, without the need to use positive or negative pressure equipment, avoiding the need to carry additional equipment for field operations. The method has a wide range of applicability to water sample volume and can achieve high-multiple enrichment of heavy metals in water. The method has a low detection limit for heavy metals in drinking water, and the detection limit for Cd, Pb, and Tl elements can reach 2μg / L, which meets the requirements for heavy metal detection in drinking water, and the spike recovery experiment verifies that the detection results of this method are highly credible. [Specific embodiment]
[0055] (I) Screening and comparison of trace heavy metal enrichment materials
[0056] 1.1 Materials and reagents
[0057] Commercial heavy metal adsorption resin materials, including:
[0058] Ion exchange resin: Dowex 50WX8 200-400(H)(Alfa Aesar (China)
[0059] Chemical Co., Ltd.), hereinafter referred to as Dowex 50WX8 resin; YW10W5 (Sichuan Changyan Technology Co., Ltd.), hereinafter referred to as YW10W5 resin; CH-97 (Kehaisi (Beijing) Technology Co., Ltd.), hereinafter referred to as CH-97 resin. Chelating resin: 2271 chelating resin disk (3M Company)
[0060] Reagents include:
[0061] Pb, Hg, Cd, Tl ion standard solutions (China Institute of Metrology);
[0062] Multi-element standard substance solutions (Al, As, B, Ba, Be, Bi, Cd, Co, Cr, Cu, Fe, Ga, Li, Mg, Mn, Ni, Pb, Sb, Sn, Sr, Ti, Tl, V, Zn)
[0063] (National Nonferrous Metals and Electronic Materials Analysis and Testing Center);
[0064] Concentrated HNO3 (67-70%) (mass spectrometry grade, Thermo Fisher Scientific).
[0065] 1.2 Instruments and Equipment
[0066] Triple quadrupole inductively coupled plasma mass spectrometer 8900 (AGILENT, USA); automatic sample injector Sps 4 (AGILENT, USA); vacuum diaphragm pump VP30 (Labtech, China); negative pressure controller (Labtech, China); aqueous filter head (0.45 μm, Hippocampus); standard sieve (pore size 0.1 / 0.2 mm, Shengfei Testing Machinery Factory, Shangyu City, Zhejiang Province); XS205DU electronic balance (Max=81g / 220g, d=0.01mg / 0.1mg, Mettler Toledo, Switzerland).
[0067] 1.3 Test of adsorption rate of heavy metal ions by enrichment materials
[0068] 1.3.1 The first test part:
[0069] 7 mg of YW10W5 resin powder with a diameter of less than 100 μm was immersed in 10 mL of mixed metal solution (Cd 5 μg / L, Pb 10 μg / L, Hg 1 μg / L and Tl 0.1 μg / L), the solvent was ultrapure water, and the mixture was shaken for 2 min. The measurement was repeated three times. 2 mL of the mixed metal solution before and after enrichment, 7.9 mL of ultrapure water and 0.1 mL of concentrated nitric acid were taken to prepare 10 mL of ICP-MS test solution after five-fold dilution. The adsorption rate of each group of resins was determined according to formula (1).
[0070] 1.3.2 The second test part:
[0071] 7 mg of YW10W5 resin powder with a diameter of less than 100 μm was soaked in 10 mL of mixed metal solutions of four concentrations. The concentrations were selected within the range of the sanitary standard limit of drinking water. The solvents were ultrapure water and tap water. The Cd concentrations were 2 μg / L, 4 μg / L, 5 μg / L, and 6 μg / L; the Pb concentrations were 4 μg / L, 8 μg / L, 10 μg / L, and 12 μg / L; the Hg concentrations were 0.25 μg / L, 0.5 μg / L, 1 μg / L, and 2 μg / L; and the Tl concentrations were 0.25 μg / L, 0.5 μg / L, 1 μg / L, and 2 μg / L. The granular resin was soaked in the solution and shaken for 2 minutes. The mixed metal solution before and after adsorption was detected by ICP-MS. The determination was repeated 3 times, and the resin adsorption rate was calculated according to formula (1).
[0072]
[0073] In formula (1), C0 is the concentration of the solution before enrichment (μg / L), and C1 is the concentration of the solution after enrichment (μg / L).
[0074] 1.3.3 The third test part:
[0075] Weigh 100 mg of CH-97, YW10W5 and Dowex 50WX8 resins respectively, and prepare 50 mL, 100 mL and 500 mL of 10 μg / L Hg, Pb, Tl and Cd mixed metal solutions, respectively, using ultrapure water and tap water. Ultrapure water is used for experiments, and tap water is drinking water. The background ions such as Ca, Mg, Zn and Sr contained in tap water are much higher than those in ultrapure water. Soak the resin in the solution and shake for 10 minutes. Take 2 mL of the mixed metal solution before and after enrichment, 7.9 mL of ultrapure water and 0.1 mL of concentrated nitric acid to prepare 10 mL of ICP-MS test solution after five times dilution. 10 mL of 1 μg / L Hg, Pb, Tl and Cd standard solution is used for single-point calibration. The adsorption rate of each group of resins is determined according to formula (1).
[0076] 1.4 Test results of adsorption rate of heavy metal ions by enrichment materials
[0077] 1.4.1 Results of the first test section
[0078] Table 1 Adsorption rate of heavy metal ions in ultrapure water with standard limit concentration of drinking water by YW10W5 resin
[0079]
[0080] *Note: Average of three measurements
[0081] As shown in Table 1, YW10W5 resin can achieve basic adsorption of trace heavy metals in ultrapure water. The adsorption rates of Cd, Tl and Pb elements are all above 90%, while the adsorption rate of Hg element is relatively low, at around 60%.
[0082] 1.4.2 Results of the second test section
[0083] When YW10W5 resin is used for enrichment of trace heavy metals in tap water, the adsorption rate varies greatly. When the concentration of the mixed metal solution is near the drinking water limit value, the adsorption of each element in tap water is greatly affected. The adsorption rate of the Tl element with the greatest impact drops from about 95% to about 20%. The Pb element with the least impact has an adsorption rate of about 90% in ultrapure water and is also reduced to 60-80% in tap water.
[0084] The reason is that, compared with ultrapure water, tap water and drinking water contain a large amount of background ions such as Ca, Mg, Zn, and Sr, which will occupy material sites during the adsorption of enriched materials, thereby affecting the adsorption and detection of trace target analytes. The background ion concentration is high. The tap water used in laboratory tests was determined by ICP-MS. The concentration of divalent Ca, Mg, Zn, and Sr ions is at the ppm level, while Pb, Cd, Hg, and Tl in the water sample are at the ppb level, which affects the adsorption of target metal ions. On the other hand, affected by the binding force of the resin functional groups, when the resin capacity is constant, if the volume of the water sample is too large, elements with strong binding force will elute elements with weak binding force, and high-content elements will elute low-content elements, which will also affect the adsorption of target metal ions.
[0085] In some examples, the main element contents in the tap water samples were Mg: 30.5 mg / L, Ca: 12.4 mg / L, Zn: 1.87 mg / L, Sr: 3.41 mg / L, and Ba: 0.104 mg / L.
[0086] 1.4.3 Results of the third test section
[0087] As shown in Table 2, YW10W5 resin has a relatively good adsorption of Hg in tap water, with adsorption rates of 90%, 74% and 55% for 50mL, 100mL and 500mL water samples, and Pb adsorption rates of 72% and 40% for 50mL and 100mL, respectively. The adsorption of Cd and Tl is relatively general, with only about half of the adsorption when the water sample volume is 50mL. At the same time, since YW10W5 resin is a mixed anion and cation resin, when the mass of different types of resins is constant, the adsorption capacity of YW10W5 resin for cations is relatively small, so the volume of the water sample has a more obvious effect on the adsorption rate.
[0088] Table 2 Adsorption rate of YW10W5 resin for 10 μg / L heavy metal ions in tap water matrix
[0089]
[0090] The YW10W5 resin has a high adsorption rate for Mg, Ca, Zn, Sr and Ba at 50 mL for the background ions in tap water, indicating that its selectivity for the target analytes is relatively poor, and the material sites are mostly occupied by background ions, which is not conducive to the adsorption of target trace heavy metal ions.
[0091] As shown in Table 3, the overall adsorption of various metal ions in tap water by Dowex 50WX8 resin decreased the most with volume. At 500mL, Cd and Tl had no adsorption rate, and Hg had the lowest adsorption rate, which was only 16% at 50mL. However, the adsorption rates of Cd and Pb were 69% and 88% at 50mL, which was better than that of YW10W5 resin.
[0092] Table 3 Adsorption of various ions in tap water by Dowex 50WX8 resin
[0093]
[0094] The adsorption rate of Dowex 50WX8 resin for major background ions such as Ca, Mg, Zn, Sr and Ba is the same as that of the target metal elements, and even partially better than that of the target trace metal elements. Combined with the data in Table 4, it shows that its selectivity for the target trace heavy metals is poor, and high concentrations of background elements have a significant impact on the target elements.
[0095] As shown in Table 4, CH-97 resin has a strong adsorption effect on Hg in 50-500mL tap water samples, and the adsorption rate remains at about 98% as the water sample volume increases to 500mL; the adsorption of Cd and Pb reaches 97-98% at 50 and 100mL, and decreases to 46% and 63% respectively as the water sample increases to 500mL; the adsorption of Tl can reach 83% at 50mL and 78% at 100mL, and decreases to 27% as the tap water sample increases to 500mL, but is still much higher than YW10W5 and Dowex 50WX8 resins as a whole. That is, when the water sample is 100mL, the selective adsorption of the target trace heavy metals can be basically achieved.
[0096] Table 4 Adsorption rate of CH-97 resin on various ions in tap water
[0097]
[0098] The adsorption rate of granular resin CH-97 to high concentrations of Mg, Ca, Sr and Ba in tap water is extremely low, which effectively avoids the influence of interfering elements on the adsorption of target metal elements. Therefore, CH-97 resin has outstanding adsorption effect on Cd, Hg and Pb with high selectivity, which meets the current research adsorption requirements.
[0099] (II) Experiment on the effect of particle size of enrichment material CH-97 on adsorption
[0100] In the present application example, CH-97 granular resin was selected as the experimental material, and the granular resin with an original particle diameter of 600-700 μm was ground into powder using a planetary ball mill, and the resin particles were screened using the various standard sieves in Table 5 to divide them into four particle sizes of 355-450 μm, 200-355 μm, 150-200 μm and 100-150 μm. 140 mg of each of the four particle sizes of CH-97 resin was weighed, and 100 mL of a mixed metal solution with a concentration of 5 μg / L was tested. The granular resin was soaked in the solution and shaken for 10 minutes. The mixed metal solution before and after adsorption was detected by ICP-MS, and the resin adsorption rate was calculated according to formula (1).
[0101] Table 5 Standard sieve mesh number and corresponding aperture size
[0102]
[0103] Table 6 shows the adsorption rate of each ion after the four particle size resins were shaken for 10 minutes. The data show that as the resin particle size decreases, the adsorption rate increases significantly, and the adsorption rate of the resin with a particle size between 100 and 150 μm is the highest among the four particle size resins. For Cd and Tl, when the resin mass is constant, the smaller the resin particle size, the faster the diffusion rate when it is shaken in water, and the greater the adsorption density. At the same time, the surface area of the small particle size resin is larger, the larger the area of contact with the water sample for adsorption, and the higher the adsorption efficiency. For Hg and Pb, relatively speaking, the adsorption rates of the four particle size resins are not much different. Therefore, on the whole, when using CH-97 granular resin for shaking adsorption, the adsorption efficiency can be increased by selecting a small particle size resin and the four ions can be adsorbed simultaneously.
[0104] Table 6 Adsorption results of four particle size resins for various ions
[0105]
[0106] (III) Effect of oscillation time on the adsorption rate of each ion
[0107] Weigh 9 portions of 30 mg of granular CH-97 resin, prepare 15 mL of mixed metal solution with 10 μg / L of Hg, Pb, Tl, and Cd in a centrifuge tube, and shake at room temperature for 0.5 min, 1 min, 2 min, 4 min, 6 min, 8 min, 10 min, 15 min, and 20 min. Take 2 mL of the mixed metal solution before and after enrichment, 7.9 mL of ultrapure water, and 0.1 mL of concentrated nitric acid to prepare 10 mL of ICP-MS test solution after five-fold dilution, and determine the adsorption rate of each group of resin according to formula (1).
[0108] Figure 1 The figure is a schematic diagram of the change in the absorption rate of heavy metals detected by granular resin CH-97 for different targets as the oscillation adsorption time increases. CH-97 resin can achieve rapid enrichment of Hg ions, which is basically completely adsorbed at 0.5 minutes, and the adsorption rate remains stable as time increases, indicating that CH-97 resin has high adsorption selectivity and strong stability for Hg. The adsorption of Pb begins to stabilize at around 2 minutes and the adsorption rate is close to 100%. The adsorption rate of Cd and Tl gradually increases with time, reaching equilibrium at around 6 and 10 minutes, respectively. Overall, the oscillation adsorption time of CH-97 granular resin is 10 minutes or more. In some examples, the oscillation adsorption time of CH-97 granular resin is selected to be 10 minutes.
[0109] (IV) Experiment on the influence of sample volume on the capacity of enrichment materials
[0110] In the present embodiment, CH-97 granular resin with a particle size of 100 to 150 μm that has been ground and sieved is selected. 140 mg of CH-97 resin is weighed, and 500 mL, 300 mL, 200 mL, and 100 mL of mixed metal solutions of Hg, Pb, Tl, and Cd with a concentration of 5 μg / L are prepared with tap water, respectively. After mixing, the mixed solutions are shaken for 10 minutes, and the filtrate is filtered out with a 0.22 μm aqueous filter membrane and then collected. The concentrations of the prepared solution and the filtrate are detected by ICP-MS, and the adsorption rate of the resin under four volumes is calculated according to formula (1).
[0111] Table 7 shows the adsorption rate of granular resin for different volumes. As the volume decreases, the adsorption rate increases significantly, and the adsorption rate of the resin for each ion is the highest when the volume is 100mL. The larger the sample volume, the worse the adsorption rate of Cd and Tl, and the worse the ability of the material to hold heavy metals; except for the lower adsorption rate of Hg when the sample volume is 500mL, there is little difference; the adsorption rate of Pb can still be above 75% when the volume is less than 300mL. Therefore, Hg and Pb can be enriched with a larger sample volume, and Cd and Tl can be enriched with a smaller sample volume.
[0112] Table 7 Results of adsorption rate of granular resin for different volumes
[0113]
[0114] (V) XRF testing
[0115] 5.1 Heavy metal enrichment and sample preparation
[0116] The granular resin is soaked in a sample bottle containing a water sample and fully shaken for a certain period of time; the liquid is filtered and the granular resin is collected to make a resin sample cake suitable for portable XRF detection, and the sample cup is detected using portable XRF.
[0117] 5.2 Sample preparation optimization in XRF testing
[0118] 5.2.1 Materials and reagents
[0119] Ion exchange resin CH-97 (Kehaisi (Beijing) Technology Co., Ltd.);
[0120] Pb, Hg, Cd, Tl ion standard solutions (China Institute of Metrology).
[0121] 5.2.2 Instruments and equipment
[0122] HDXRFE-max500 single-wavelength excitation EDXRF (Suzhou Jiapu Technology Co., Ltd.); pre-enrichment system (enrichment head, syringe, enrichment pump PreC-500, Suzhou Jiapu Technology Co., Ltd.); solid phase extraction device Qprep (China Labtech Company); vacuum diaphragm pump VP30 (China Labtech Company); negative pressure controller (China Labtech Company); replaceable membrane syringe filter (13mm, Millipore Company, USA); XS205DU electronic balance (Max=81g / 220g, d=0.01mg / 0.1mg, Mettler Toledo Company, Switzerland); electric heating blast drying oven (Shanghai Yiheng Scientific Instrument Co., Ltd.).
[0123] 5.2.3 Thickness of granular resin samples
[0124] Another important feature in XRF analysis is the effective thickness of the sample being measured, which is determined by the density of the sample and its ability to absorb characteristics. The greater the energy of the element's characteristic spectral line, the less loss of the element's characteristic X-ray fluorescence in the process of penetrating the filter membrane to reach the detector; but the matrix effect caused by the increase in the thickness of the thin film sample is stronger, the background fluorescence intensity at the corresponding characteristic spectral line position is greater, and the matrix effect caused by the increase in sample thickness has a greater impact on the sensitivity of thin film XRF spectrum measurement. Therefore, for elements with higher characteristic spectral line energy (energy>7keV), the sensitivity of XRF spectrum measurement can be improved by appropriately increasing the sample thickness to increase the mass thickness concentration of the component being measured. The target analytes Cd, Hg, Tl and Pb are all elements with higher characteristic spectral line energy.
[0125] 1g of CH-97 resin was soaked in 500mL of 50μg / L mixed metal solution of Hg, Pb, Tl, and Cd, with ultrapure water as the solvent, and shaken for 20min. The resin was enriched and dried by vacuum filtration using a solid phase extraction device. Resin samples with no resin, 1mm, 1.5mm, 2mm, 3mm, 4mm, and 5mm thickness were selected and filled into the sample cup with a diameter of 8mm. After compaction, the top was sealed with a plastic film. The samples were measured three times by monochrome XRF, and the detection mode was underwaterplus to evaluate the influence of sample thickness on the actual measurement.
[0126] The matrix effect is due to the different types and contents of interfering elements in the sample to be tested, and some interfering elements have an absorption or enhancement effect on the X-ray fluorescence of the target element to be tested. As mentioned in the previous article, the greater the energy of the element's characteristic spectral line, the less loss of the element's characteristic X-ray fluorescence in the process of penetrating the filter membrane to reach the detector, but at the same time, the matrix effect caused by the increase in the thickness of the thin film sample is stronger, and the background fluorescence intensity at the corresponding characteristic spectral line position is greater. It can be seen that the slowdown in the growth of the target element count value is partly due to the balance between the growth of the target object's fluorescence intensity and the matrix effect.
[0127] Figure 2 The figure is a schematic diagram showing the effect of the thickness of the resin disc made of granular resin CH-97 on the count values of each ion. The count value of granular resin CH-97 basically increases with the thickness at 0-2mm, and gradually stabilizes at 2-6mm, indicating that the characteristic spectral line intensity and matrix effect that increase with thickness reach a balance at about 2mm. The thickness of the resin disc made of the resin granular sample is set to 2-3mm. In some embodiments, the thickness of the resin granular sample is set to 3mm.
[0128] In other examples, the granular resin CH-97 enriched with heavy metals was made into resin round cakes to be tested, the thickness of the resin round cakes to be tested was 2 to 3 mm, and further the thickness of the sample cakes to be tested was 3 mm.
[0129] 5.2.4 Effect of sample diameter on XRF detection
[0130] The granular resin CH-97 was loaded on a solid phase extraction device to enrich 500mL of a mixed metal solution of 50μg / L Cd, Hg, Tl and Pb, and the solvent was ultrapure water. The enriched granular resin was made into disk samples with diameters of 0mm, 3mm, 6mm, 8mm and 10mm, respectively. The portable monochrome XRF measured the disk samples with different diameters three times, and the detection mode was underwater-plus to evaluate the effect of sample diameter on the actual XRF measurement.
[0131] Figure 3 The figure is a schematic diagram of the effect of different sample diameters on monochromatic XRF measurement. As the diameter of the resin sample increases, the count value of the monochromatic XRF increases continuously. The monochromatic XRF spot diameter used in the experiment is 3mm. When the diameter of the resin sample exceeds the diameter of the X-ray spot, the recovery of the characteristic spectral lines reflected by the sample due to the excitation of the rays decreases. When the diameter is 10mm, the rise of the monochromatic XRF count value slows down significantly, and its slope is less than when the diameter is 8mm, indicating that the diameter of the resin sample has reached the edge of the spot. Combined with the actual sample preparation and detection requirements, the optimal value of the particle resin sample CH-97 is 8mm, which can effectively utilize the detection rays of the portable monochromatic XRF.
[0132] 5.2.5 Effect of drying treatment on XRF detection
[0133] The granular resin CH-97 was enriched with mixed metal solutions of different concentrations of Cd, Hg, Tl and Pb (the concentrations of each heavy metal were 0, 10 and 20 μg / L respectively), and the solvent was ultrapure water. The enriched granular resin was made into discs with the same diameter and thickness for testing. After the samples were prepared, they were dried in different ways. The first group was directly tested by XRF without drying, the second group was dried by light suction with filter paper, and the third group was dried by drying at 50°C for 15 minutes.
[0134] Figure 4 The figure shows the change of the monochromatic XRF count values of different heavy metals under different drying methods. As the drying degree of the sample increases, the monochromatic XRF count values of Cd, Tl and Pb increase significantly. Figure 4 A represents direct measurement without drying, B represents light suction with filter paper, and C represents drying (15 minutes at 50°C). At the same time, as the concentration increases, the difference in count values increases significantly. The three methods of measuring Hg are not much different, but at 20μg / L, light suction with filter paper and drying methods are greater than direct measurement. Overall, drying resin samples is beneficial to improving and stabilizing the measurement signal of monochrome XRF.
[0135] (VI) Method evaluation
[0136] 6.1 Materials and reagents
[0137] Ion exchange resin CH-97 (Kohais (Beijing) Technology Co., Ltd.); Pb, Hg, Cd, Tl ion standard solutions (China Institute of Metrology); concentrated HNO3 (67-70%) (mass spectrometry grade, Thermo Fisher Scientific Co., Ltd.).
[0138] 6.2 Instruments and Equipment
[0139] HDXRFE-max500 single wavelength excitation EDXRF (Suzhou Jiapu Technology Co., Ltd.); pre-enrichment system (enrichment head, syringe, enrichment pump PreC-500) (Suzhou Jiapu Technology Co., Ltd.); triple quadrupole inductively coupled plasma mass spectrometer 8900 (AGILENT, USA); automatic sample injector Sps 4 (AGILENT, USA); replaceable membrane syringe filter (13 mm, Millipore, USA); XS205DU electronic balance (Max = 81 g / 220 g, d = 0.01 mg / 0.1 mg, Mettler Toledo, Switzerland)
[0140] 6.3 Determination of standard curve
[0141] A mixed heavy metal solution of Cd, Hg, Tl and Pb with a volume of 100 mL and concentrations of 0.5 μg / L, 1 μg / L, 2 μg / L, 3 μg / L, 5 μg / L, 10 μg / L, 15 μg / L, 20 μg / L and 25 μg / L was prepared; 9 portions of 140 mg of granular resin CH-97 were prepared; 100 mL of the mixed heavy metal solution was enriched by granular resin vibration adsorption to obtain a series of resin samples with different heavy metal enrichment amounts, which were dried and sealed for storage.
[0142] 6.4 Determination of detection limit
[0143] 6.4.1 Detection limit determination steps
[0144] According to the actual measurement results, appropriate low-concentration samples were selected, with tap water as the solution matrix, Cd, Hg, Tl, and Pb as the target analytes, and granular resin was used for seven repeated samplings, and each sample was tested three times. The limit of detection (LOD) and limit of quantification (LOQ) were calculated based on the slope of the standard curve of each heavy metal ion and the arithmetic mean of the sample count value. The calculation formulas are (2) to (6):
[0145]
[0146] Where: SD is the standard deviation between repeated test results; AM is the arithmetic mean of repeated test results; k is the slope of the standard curve equation.
[0147] 6.4.2 Detection limit determination results
[0148] The initial concentration of heavy metal ions in the standard sample C0 (μg / L) is taken as the horizontal axis, and the corresponding count value Intensity (Counts) detected in the standard sample by monochrome XRF is taken as the vertical axis. The detection result of each standard sample is expressed in the form of a scatter plot in the coordinate system, and a linear regression equation is fitted to obtain the standard curve of the initial concentration of each heavy metal ion and the count value of the particle resin oscillation method. The results are shown in Table 8 Standard curve data and Figure 5 The standard curves of initial concentrations of each heavy metal ion and count values are shown in FIG.
[0149] Table 8 Standard curve data
[0150]
[0151] Note: The measurement was averaged three times.
[0152] The method detection limit of Cd is 2μg / L, which is lower than the limit of 5μg / L in the sanitary standard for drinking water (GB5749-2022), indicating that this method has good performance in the detection of trace Cd and is suitable for the detection of trace heavy metals in tap water. The method detection limit of Tl is 2μg / L, indicating that this method has certain performance in the detection of trace Tl. The method detection limit of Pb is 2μg / L, which is below the limit of 10μg / L in the sanitary standard for drinking water, meeting the needs of trace Pb detection in water samples. During the determination of the standard curve, the highest concentration point is 25μg / L, and the count value of Hg ions has obvious differences starting from the concentration point of 20μg / L. There is no stable signal at the previous concentration points, indicating that the detection limit of Hg ions by the granular resin oscillation method is higher than 20μg / L.
[0153] However, in the material screening part, the selected granular resin can adsorb Hg in tap water at a rate of about 98%, indicating that Hg ions have been basically enriched in the material. The reason for this is that different elements have different stability and signals in XRF detection, Hg ions themselves have poor stability, and the preparation method of the resin sample cake (internal compactness) has a greater impact on its detection, thereby affecting the detection of Hg ions.
[0154] Therefore, the ion detection limits of Cd, Hg, Tl and Pb are: 2μg / L for Cd, greater than 20μg / L for Hg, 2μg / L for Tl, and 2μg / L for Pb.
[0155] 6.5 Determination of method spike recovery
[0156] 6.5.1 Method spike recovery test operation
[0157] 1. Prepare standard curve solution
[0158] Use Cd, Hg, Tl, and Pb ion standard solutions to prepare standard curve solutions at concentration points of 1, 2, 5, 10, and 20 μg / L, with 100 mL of each solution and tap water as the solvent.
[0159] 2. Preparation of spiked samples
[0160] According to the quantitative limit of the particle resin oscillation method, the concentration of the spiked sample was determined as follows: Cd 5μg / L, Hg 15μg / L, Tl 5μg / L, Pb 8μg / L. The particle resin oscillation method was used to prepare the stock solution resin sample and the spiked resin sample.
[0161] 3. Fitting the linear regression equation The standard curve resin sample was prepared by the enrichment method of the granular resin oscillation method, and the Cd, Hg, Tl, and Pb in the standard resin sample were determined by portable monochrome XRF. The linear regression equation was fitted with the initial concentration of heavy metal ions C0 (μg / L) in the standard sample as the horizontal axis and the corresponding count value Intensity (Counts) detected in the standard sample by monochrome XRF as the vertical axis.
[0162] 4. Calculate the recovery rate
[0163] The initial concentrations Ca and Cb of Cd, Hg, Tl and Pb in the original solution and spiked resin samples were calculated based on the count values of the original solution and spiked resin samples and the linear regression equation, and the recovery rate of the spiked sample was calculated according to formula (7).
[0164]
[0165] Where P is the recovery rate, %; Ca is the concentration measured in the spiked water sample; Cb is the concentration measured in the original water sample; C0 is the concentration of the added standard.
[0166] The detection principle of X-ray fluorescence spectroscopy is based on the transition process of electrons outside the nucleus of an atom. When electrons outside the nucleus transition from a high energy level to the K layer, the X-rays emitted are called K series (K α1 , K α2 , K β1 , K β2 ) spectral line; the rays produced when transitioning to the L layer are called L series (L α1 , L α2 , L β1 , L β2 ) spectral line. Each ion's unique spectral line has a fixed energy value. By measuring the X-ray fluorescence energy scattered after the target substance is excited, accurate qualitative and quantitative analysis of the elemental ions contained therein can be performed.
[0167] However, X-ray fluorescence spectroscopy often faces the problem of peak overlap in application. For example, the M α K peak and S ion α The radiation energies of the peaks are 2.34 KeV and 2.30 KeV respectively. Since the two energies are similar, if the K α The peak of As ions is used as a quantitative or qualitative standard and may be seriously interfered by Pb ions. α (10.531KeV) and L of Pb ions α(10.541KeV) also has a similar energy overlap problem, but since As ions are enriched by anion resin and Pb ions are enriched by cation resin, this interference factor is effectively eliminated in the embodiment of the present application. For the four target ions of Cd, Hg, Tl and Pb in the embodiment of the present application, the K of Cd was selected respectively. α Peak, Hg L α Peak, Tl L α Peak and Pb L α Peaks are used as qualitative and quantitative standards for portable monochrome XRF testing of resin samples. Through this selection strategy, the interference of other element ions can be avoided to the greatest extent, ensuring the accuracy and reliability of the test results. In order to reduce the error of uneven loading of heavy metal ions on the surface of resin samples, when using portable monochrome XRF testing, the resin sample is randomly rotated to take 3 points for testing, and the arithmetic mean of the heavy metal ion signal values obtained from the test is calculated as the final result.
[0168] 6.5.2 Result Analysis
[0169] As shown in Table 9, this study used national metal ion standard samples as a benchmark and prepared actual spiked water samples by dilution. The recovery rates of Cd, Tl, and Pb in spiked tap water samples using the on-site XRF detection method for trace heavy metals in drinking water provided by the embodiment of the present application were between 84% and 117%, indicating that the analytical method has good credibility.
[0170] Table 9 Spiked recovery results
[0171]
[0172] The present application provides a method for rapid on-site detection of trace heavy metals in drinking water. The method uses heavy metal particle enrichment resin to perform dispersed solid phase extraction on heavy metals in drinking water, and uses XRF to detect heavy metal elements adsorbed by the resin, which can achieve rapid enrichment and detection of trace heavy metals in drinking water, and has the characteristics of being able to detect multiple heavy metals (Cd, Tl, Pb, Hg) at the same time, and high sensitivity. The present application uses a dispersed solid phase extraction method, and can apply the heavy metal enrichment particle resin materials already available on the market, without the need to specially develop specific materials, which expands the scope of application and ease of use of the technology. The enrichment material can be collected by hand-squeezing the sample bottle in combination with a filter to avoid carrying positive or negative pressure equipment. The method can be used for heavy metal enrichment in large-volume water samples, and can achieve high-multiple enrichment of low-content heavy metals in water. The method has a low detection limit for heavy metals in drinking water, and the detection limit for Cd, Pb, and Tl elements can reach 2μg / L, which meets the requirements for heavy metal detection in drinking water. The spike recovery experiment verifies that the detection results of the method are highly credible.
[0173] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A method for rapid on-site detection of trace heavy metals in drinking water, characterized in that: Adding heavy metal-enriched granular resin into a sample-loading bottle containing drinking water, and fully shaking for a first preset time, so that the heavy metal-enriched granular resin as a dispersed solid phase can enrich and extract trace heavy metals in the drinking water, collecting the heavy metal-enriched granular resin to prepare a sample to be tested, using XRF to detect the heavy metal signal of the sample to be tested, and calculating the heavy metal content in the water; The drinking water includes drinking water and water for human life.
2. The on-site rapid detection method for trace heavy metals in drinking water according to claim 1, characterized in that: The heavy metal enrichment granular resin is an ion exchange resin or a chelating resin; Preferably, the heavy metal-enriched granular resin is an ion exchange resin containing a methyl mercaptan functional group; Preferably, the heavy metal-enriched granular resin is Cohis CH-97 resin.
3. The heavy metal-enriched granular resin according to claim 2, characterized in that: The particle size of the heavy metal enriched granular resin ranges from 75 to 450 μm.
4. The on-site rapid detection method for trace heavy metals in drinking water according to claim 1, characterized in that: The volume range of the drinking water is 15 to 500 mL.
5. The on-site rapid detection method for trace heavy metals in drinking water according to claim 1, characterized in that: The first preset duration ranges from 2 to 20 minutes; Preferably, the first preset time length is 10 minutes.
6. The heavy metal-enriched granular resin according to claim 2, characterized in that: The sample to be tested made of the heavy metal-enriched granular resin is a round cake with a thickness of 2 to 6 mm and a diameter of 3 to 10 mm; Preferably, the thickness of the sample to be tested is 2 to 3 mm; Preferably, the sample to be tested has a thickness of 3 mm and a diameter of 8 mm.
7. The sample to be tested according to claim 6, characterized in that: After drying, use XRF for testing; Preferably, the sample to be tested is dried by absorbing water with filter paper or by drying.
8. The on-site rapid detection method for trace heavy metals in drinking water according to claim 1, characterized in that: XRF is a monochromatic portable X-ray fluorescence spectrometer.
9. The method for detecting trace heavy metals in drinking water according to claim 1, characterized in that: The heavy metal includes at least one element of Cd, Tl, Pb, and Hg; Preferably, the heavy metal includes at least one element selected from the group consisting of Cd, Tl and Pb.